Agronomy vs agroecology: should we abandon the pursuit of improving agronomic practices in favour of promoting agroecology? - Theodore M. DeJong (European Journal of Horticultural Science)
Abstract There has recently been discussion about the need to abandon traditional agronomy research directed towards making our agricultural systems more environmentally, economically and socially sustainable using plot-sized experiments in favour of more systems-based agroecology research. Agroecology promotes biodiversity and ecological principles to create productive plant communities that rely on natural processes for supplying nutrients and controlling pests and diseases. This brief commentary examines the definitions of both approaches to improving agricultural production systems and points out that the goals of both types of research are similar, but the means for achieving the goals are significantly different. The agronomy approach promotes incremental improvements of existing systems, whereas agroecological approaches promote abandoning traditional agronomic systems and replacing them with complex managed, biodiverse, plant communities. Impediments to developing entirely new biodiverse agroecologically based production systems compared with focusing on improving current agronomic systems to improve the long-term sustainability of crop productions are discussed. Significance of the study What is already known on this subject? This subject is not new; however, there is currently some confusion about the difference between agronomy and agroecology and whether the former should be abandoned in favour of the latter. What are the new findings? This article does not present new information but attempts to address the above-mentioned confusion and suggests that both approaches are valid, but more progress has been made with substitutionary agronomic approaches. What are the expected impacts on horiticulture? Hopefully, this will clarify how agronomy and agroecology approaches to horticulture research differ but also help recogniton that both approaches are valid.